2014
DOI: 10.1101/gad.230045.113
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAPK overrides the termination of myelin growth and replaces Nrg1/ErbB3 signals during Schwann cell development and myelination

Abstract: Myelination depends on the synthesis of large amounts of myelin transcripts and proteins and is controlled by Nrg1/ErbB/Shp2 signaling. We developed a novel pulse labeling strategy based on stable isotope labeling with amino acids in cell culture (SILAC) to measure the dynamics of myelin protein production in mice. We found that protein synthesis is dampened in the maturing postnatal peripheral nervous system, and myelination then slows down. Remarkably, sustained activation of MAPK signaling by expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
131
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(150 citation statements)
references
References 55 publications
15
131
1
3
Order By: Relevance
“…Furthermore, ablation of Erk1/2 in Schwann cells causes deficits that are remarkably similar to those observed in Shp2 or Nrg1/ErbB2/ErbB3 mutants (Newbern et al, 2011). Interestingly, mild activation of MAPK signaling releases Schwann cells from their dependence of Nrg1 signaling during all stages of Schwann cell development and myelination (Sheean et al, 2014). In particular, MAPK/Erk positively regulate entry into myelination but a strong and sustained activation of Raf (and thus the Ras/MAPK/Erk cascade) results in demyelination, indicating that signaling strength determines the cellular response (Napoli et al, 2012).…”
Section: Nrg1 and Other Extrinsic Signals That Control Myelinationmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, ablation of Erk1/2 in Schwann cells causes deficits that are remarkably similar to those observed in Shp2 or Nrg1/ErbB2/ErbB3 mutants (Newbern et al, 2011). Interestingly, mild activation of MAPK signaling releases Schwann cells from their dependence of Nrg1 signaling during all stages of Schwann cell development and myelination (Sheean et al, 2014). In particular, MAPK/Erk positively regulate entry into myelination but a strong and sustained activation of Raf (and thus the Ras/MAPK/Erk cascade) results in demyelination, indicating that signaling strength determines the cellular response (Napoli et al, 2012).…”
Section: Nrg1 and Other Extrinsic Signals That Control Myelinationmentioning
confidence: 72%
“…Such studies mainly implicated PI3K/Akt as key signals in myelination, and suggested that MAPK/Erk played a limited role or even drive Schwann cells into dedifferentiation (Maurel and Salzer, 2000;Harrisingh et al, 2004;Ogata et al, 2006). Unexpectedly, recent genetic experiments have now shown that MAPK/Erk signaling is a major positive regulator of myelination in vivo, indicating that this notion has to be revisited (Grossmann et al, 2009;Newbern et al, 2011;Ishii et al, 2013;Sheean et al, 2014).…”
Section: Nrg1 and Other Extrinsic Signals That Control Myelinationmentioning
confidence: 99%
“…Although myelin proteins and lipids are probably overall relatively stable, in the long term they appear to be exchanged substantially according to a study conducted on human postmortem brain samples (Yeung et al, 2014). Of note, studies on myelin turnover in the PNS are rather scarce at this time and require further research attention (Sheean et al, 2014). …”
Section: Myelination and Metabolismmentioning
confidence: 99%
“…The major outcomes of the loss‐ and gain‐of‐function studies on the roles of mTORC1 and the upstream PI3K‐Akt and Mek‐Erk1/2 pathways in PNS and CNS myelination are summarized (Beirowski et al, 2017; Bercury et al, 2014; Carson et al, 2015; Cotter et al, 2010; Domenech‐Estevez et al, 2016; Figlia et al, 2017; Flores et al, 2008; Fyffe‐Maricich, Karlo, Landreth, & Miller, 2011; Fyffe‐Maricich, Schott, Karl, Krasno, & Miller, 2013; Goebbels et al, 2010, 2012; Ishii, Furusho, & Bansal, 2013; Ishii, Furusho, Dupree, & Bansal, 2016; Jeffries et al, 2016; Jiang et al, 2016; Lebrun‐Julien et al, 2014; Napoli et al, 2012; Newbern et al, 2011; Norrmén et al, 2014; Sheean et al, 2014; Sherman et al, 2012; Wahl et al, 2014; Zou et al, 2011, 2014)…”
Section: Myelination and Mtormentioning
confidence: 99%
See 1 more Smart Citation